PENGEMBANGAN MEDIA PEMBELAJARAN FLIBET (FLIPBOOK ALFABET) UNTUK MEMBACA NYARING (READING ALOUD) SISWA KELAS 1 SD N PETERONGAN SEMARANG - Meira Erlina Hapsari; Mudzanatun S.Pd., M.Pd.; Asep Ardiyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is based on the difficulty of reading aloud (reading aloud) of students in class I of SD Negeri Peterongan Semarang, which is characterized by difficulties in recognizing letters, pronouncing words, and lack of confidence when reading. In addition, the use of conventional learning media causes learning to be less interesting and less effective in improving early literacy skills. Therefore, it is necessary to develop learning media that is innovative, interesting, and in accordance with the characteristics of lower grade students, one of which is through the Flibet (Alfabet Flipbook) media. This research aims to find out the feasibility and practicality of the Flibet (Alfabet Flipbook) learning media for reading aloud (reading aloud) 1st grade students of SD Negeri Peterongan Semarang. This research uses the Research and Development (R&D) method with the ADDIE model stage (Analyis, Design, Development, Implementation, Evaluation. Research subjects include media experts, material experts, first grade teachers, and first grade students of Peterongan State Elementary School Semarang. The research results show that the Flibet learning media (Flipbook Alphabet) has obtained a very high level of eligibility with a media expert validation percentage of 99.2% and 94.4% which is included in the very worthy category, as well as a material expert validation percentage of 99.17% and 95.83% which is included in the very decent category. In addition, the results of the practicality test showed that the teacher's response obtained a percentage of 85.33% and the student's response of 91.11%, both of which were included in the very practical category. This media is considered interesting, easy to use, and able to help students in recognizing letters, pronouncing words, and reading aloud with more confidence. Thus, the Flibet learning media (Alfabet Flipbook) is declared very suitable and very practical to be used as a supporting medium for learning to read aloud for primary school first grade students.